(NkOLEBATELXNO(B-(NWRA]ATELXNAQ SPEKTROSKOPIQ WODQNOGO PARA (B/s - (NbYKOW(B, (NaLEKSANDR dMITRIEWI^s; (NmAKU[KIN(B, (N`RIJ sEMENOWI^s; (NuLENIKOW(B, (NoLEG nIKOLAEWI^s; (NkABANOW(B, (Nm(B.(Nw(B.s ((NnOWOSIBIRSK (B:s (NnAUKA(B. (NsIB(B. (NOTD(B-(NNIE(B,s, 1989)
(NbIBLIOGR(B. 385 (NNAZW(B.s
(Nan sssr(B, (NsIB(B. (NOTD(B-(NNIE(B, (NiN(B-(NT OPTIKI ATMOSFERYs
Keywords: (NwODQNOJ PAR s -- (NsPEKTROSKOPI^ESKIE ISSLEDOWANIQs